REVIEW OF SPECIES CAULERPA AND CAULERPELLA (CHLOROPHYTA, BRYOPSIDALES) FROM VIETNAM - Tri, P. H. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2009)
Caulerpa and Caulerpella, the two genera belonging to the phylum Chlorophyta, order Bryopsidales distribute generously along the coast and islands of Vietnam. Based on the collected specimens, twenty-seven taxa belonging to the genus Caulerpa Lamouroux and one species of Caulerpella Prudhomme van Reine and Lokhorst are described and illustrated. The list of species includes: Caulerpa brachypus, C. cupressoides, C. fastigiata, C. lentillifera, C. mexicana, C. microphysa, C. nummularia, C. peltata, C. racemosa, C. serrulata, C. sertularioides, C. taxifolia, C. urvilliana, C. verticillata, C. webbliana and Caulerpella ambigua.